Pasang Surut Demokrasi Indonesia (1945-1965) - Dedi Asmara; Yuhardi Yuhardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to explain how the journey of Indonesian democracy from the early days of the independence of the Republic of Indonesia to the end of guided democracy. This study uses historical research methods. The results of the research show that August 17, 1945 was the independence day of the Republic of Indonesia which was successfully proclaimed. With the founding of the new Indonesia, rules and order for the life of the nation and state are needed. Thanks to the persistent efforts of the founding fathers of the Indonesian nation, they managed to formulate a law known as the 1945 Constitution. When the Netherlands recognized Indonesian sovereignty in 1949, the Indonesian nation faced a new political atmosphere. Various kinds of political conditions occurred, ranging from cabinet changes, political ideological feuds between religious, nationalist and socialist groups, to the domination of one particular group that tried to perpetuate power. The conclusions of the research show that since its establishment Indonesia has started to experience various problems in politics which have made Indonesia more mature in politics Keywords: Democracy, Politics, Power.